Re-enacting the international order, or: why the Syrian state did not disappear. Issue 5 (28th December 2021) - Grzybowski, Janis
Abstract: At the height of the Syrian civil war, many observers argued that the Syrian state was collapsing, fragmenting, or dissolving. Yet, it never actually vanished. Revisiting the rising challenges to the Syrian state since 2011 – from internal collapse through external fragmentation to its looming dissolution by the 'Islamic State' – provides a rare opportunity to investigate the re-enactment of both statehood and international order in crisis. Indeed, what distinguishes the challenges posed to Syria, and Iraq, from others in the region and beyond is that their potential dissolution was regarded as a threat not merely to a – despised – dictatorial regime, or a particular state, but to the state-based international order itself. Regimes fall and states 'collapse' internally or are replaced by new states, but the international order is fundamentally questioned only where the territorially delineated state form is contested by an alternative. The article argues that the Syrian state survived not simply due to its legal sovereignty or foreign regime support, but also because states that backed the rebellion, fearing the vanishing of the Syrian nation-state in a transnational jihadist 'caliphate', came to prefer its persistence under Assad. The re-enactment of states and of the international order are thus ultimately linked.